Breaking the Indonesian Local Leaders' Problem: A Comparative Analysis of Direct and Indirect Local Leader's Elections in Indonesia and India - Gugun El Guyanie (Faculty of Law, Universitas Sebelas Maret, 2025)
Strategic political and constitutional legal issues affect Indonesian local leaders' positions. With over 500 provinces, regencies, and cities, each region has unique capabilities impacted by several factors, making direct local leader election unfeasible for all places. The study uses comparative legal theory to compare direct regional head elections to Regional House of Representatives elections. This study uses comparative legislation to analyze the Regional House of Representatives direct election paradigm of local leaders. This study shows the need to link local leader electoral options with regional capacity characteristics. The study compared eleven variables with positive and negative features, either directly or through local leaders' Regional House of Representatives elections. Democracy is implemented according to regional capability indicators in both models. Comparing the electoral systems for local leaders in Indonesia and India shows that an asymmetric model that accounts for geographical, sociological, and cultural factors can uncover clustering in direct and indirect elections. Regional capacities and disparities prevent standardizing the regional election model. The local leader's electoral options should be revised according to geographical heterogeneity